2019
DOI: 10.1088/1755-1315/365/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Physical quality change of rose tea during freeze drying

Abstract: Rose tea began to be widely developed since it has advantages in the form of high antioxidant content, and fragrant aroma. Currently, rose tea production uses manual dryers in the form of sunlight energy, which might reduce the physical and chemical quality of rose tea. The low temperature drying is expected to be able to maintain the quality of rose tea. The aim of the study was to determine the drying characteristics of rose tea using a freeze dryer machine. The material used is a local type of rose petals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Therefore, this drying method exhibits significant potential for application in rose herbal tea production. Imaniar et al (2019) conducted a study to compare the quality of freeze-dried rose petals with those dried using an oven and sunlight. The outcomes showed that freeze-dried rose exhibited brighter colors and lower final moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this drying method exhibits significant potential for application in rose herbal tea production. Imaniar et al (2019) conducted a study to compare the quality of freeze-dried rose petals with those dried using an oven and sunlight. The outcomes showed that freeze-dried rose exhibited brighter colors and lower final moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that LTD is a drying technology that allows the product to change very little from its original state [12]. Previous research found that low-temperature freeze-dried rose tea, compared to dryer-dried, not only had improved physicochemical properties, but the color of the tea could also be retained better [13]. HAD and LTD have also been widely used in some vegetables and fruits [14], such as garlic, maoberry fruits, and lemon [15][16][17].…”
Section: Introductionmentioning
confidence: 99%